PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE KANCING GEMERINCING DAN DISIPLIN BELAJAR TERHADAP HASIL BELAJAR EKONOMI SISWA KELAS X DI SMA NEGERI 3 KOTA SOLOK - Revita Yuni (Jurnal Educative: Journal of Educational Studies, 2016)
Abstract The research was background by student’s of result of class X student studying economics at SMAN 3 Solok still low. In this case, the teacher is still using lecture and discussion methods in teaching and learning. In the discussion of the method is still often a child is passive and resigned to it in his more dominant at the time of group discussion. One of the way that can use to problem solve, it’s cooperative learning of gemerincing button type. Purpose of this study economics student learning outcomes using cooperative learning of gemerincing button type better than conventional learning models in X grade at SMA Negeri 3 Solok. The types of quasi-experimental research is the subject of purposive sample. The data used was obtained by ANOVA analysis used two lines. Based on data analysis, SPSS 20, with a probability value of 0.000. Thus, we can conclude the results of the economic study of students taught with cooperative learning economics learning outcomes students who were taught by using cooperative learning of gemerincing button type had higher outcomes than students who were taught by using conventional model in X grade at SMA Negeri 3 Solok, the trust level is 95%. Key Word: Model Pembelajaran Kooperatif Tipe Kancing Gemerincing, Disiplin Belajar, Hasil Belajar Ekonomi